The anxienty of speaking English ability in ICT usage as media TEFL on nursing students of STIK Bina Husada Palembang - Arief Pamuji (Language and Education Journal, 2020)
The objective of this research was to find out the description of the anxiety of speaking English ability in ICT usage as media TEFL on nursing students of STIK Bina Husada Palembang. , The sample of this research was taken by using a totaling sampling technique with 18 nursing students of the 3rd semester. The data was obtained from questionnaires and speaking tests in one day. Then from the data analysis, it’s obtained that there was based on a questionnaire from 18 students, the study result showed that 1 student never felt anxiety and 2 felt very often. The use of ICT helps them more confidence that form 1 students become 1 student who was in high and 6 in low anxiety level rather than the use of face to face learning that students had a high level in anxiety. The result of the study also obtained the scoring of students’ speaking that all of the students got upper 60 and the highest score from 18 students was 97. The participation of students in zoom or google meetings can be assumed that ICT usage can help the students more active because they can find many sources to develop their knowledge easily and make them more confident.